Thermophysical property measurements and thermal energy storage capacity analysis of aluminum alloys. (1st November 2016) - Wei, Gaosheng; Huang, Pingrui; Xu, Chao; Liu, Dongyu; Ju, Xing; Du, Xiaoze; Xing, Lijing; Yang, Yongping
Highlights: The thermophysical properties of aluminum alloy samples were experimental studied. The effect of element addition and temperature on properties of PCMs were analyzed. The formulas were recommended to estimate temperature dependent properties. The heat storage capacities in different samples were compared. Abstract: Ten aluminum alloy samples are prepared using a casting method by carefully designing compositions of Al-Si, Al-Cu, Al-Mg, and Al-Cu-Zn alloys. This paper measures the phase change temperature, latent heat, and specific heat of the samples using a differential scanning calorimeter (DSC), the thermal diffusivity using a laser flash method, and derives the thermal conductivity of each sample. The effects of element addition and temperature on the performance of the aluminum alloy phase change materials (PCM) are comprehensively analyzed. The thermal energy storage (TES) capacities of the samples in different temperature ranges are also analyzed. The results show that adding Cu, Zn, and Si to an aluminum alloy helps reduce the melting point of the alloy. The addition of dense elements such as Cu and Zn in aluminum alloys improves the alloy's TES capacity per volume unit. Based on experimental results, this paper also recommends fitting formulas for calculating the temperature dependent specific heat and thermal conductivity of the aluminum alloys studied.